2021
DOI: 10.1136/jitc-2020-002014
|View full text |Cite
|
Sign up to set email alerts
|

Copy number loss in granzyme genes confers resistance to immune checkpoint inhibitor in nasopharyngeal carcinoma

Abstract: BackgroundAnti-programmed death (PD)-1 therapy has recently been used in recurrent or metastatic (R/M) nasopharyngeal carcinoma (NPC). The long-term survival and its biomarkers responding to anti-PD-1 treatment in patients with R/M NPC remain unclear.MethodsPatients with R/M NPC were enrolled between March 2016 and January 2018 from two phase I clinical trials. The median follow-up period was 24.7 months. Eligible patients progressed on standard chemotherapy had measurable disease by Response Evaluation Criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In NPC clinical trials, the copy number gain of the cytotoxic effectors, GZMB and GZMH, was associated with increased survival during anti-PD1 treatment. 57 Thus, in rNPC samples, with elevated cytotoxic and exhausted features, there were sufficient evidence to conjecture rNPC respond better in ICI than primary tumor.…”
Section: Discussionmentioning
confidence: 98%
“…In NPC clinical trials, the copy number gain of the cytotoxic effectors, GZMB and GZMH, was associated with increased survival during anti-PD1 treatment. 57 Thus, in rNPC samples, with elevated cytotoxic and exhausted features, there were sufficient evidence to conjecture rNPC respond better in ICI than primary tumor.…”
Section: Discussionmentioning
confidence: 98%
“…Granzyme B is a serine protease released by CD8 + T cells and natural killer cells and functions as a downstream effector of tumor cytotoxic T cells 17,18 . A recent study found that alterations in the Granzyme B gene (GZMB/H) negatively predicted ICB e cacy in nasopharyngeal cancer patients 19 . Thus, the role of Granzyme B protein as a biomarker was investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the expression of HLAB gene, which was also part of the HLA complex, was reportedly associated with tumor progression in CRC [31]. Furthermore, ARHGEF1, CFAP65, PDGFRB and CLEC5A were labeled as prognostic marker by the Human Protein Atlas in renal and breast cancer, endometrial cancer, renal and urothelial cancer, and ovarian cancer, respectively [32,33]. The predictive model established through LASSO and LOOCV was based on 23 DMRs, most of them were located in the gene coding or promoter regions.…”
Section: Discussionmentioning
confidence: 99%